Unconventional Central Bank Measures for Emerging Economies - Stone, Mark (IMF Working Papers; Working Paper ;, 2009)
Unconventional central bank measures are playing a key policy role for many advanced economies in the 2007-09 global crisis. Are they playing a similar role for emerging economies? Emerging economies have widely used unconventional foreign exchange and domestic short-term liquidity easing measures. Their use of credit easing and quantitative easing measures has been much more limited. Thus, unconventional measures are much less important for emerging economies compared to advanced economies in achieving broader macroeconomic objectives. The difference can be attributed to the relatively limited financial stress in emerging economies, their external vulnerabilities and their limited scope for quasifiscal activities.